2013
DOI: 10.1159/000355909
|View full text |Cite
|
Sign up to set email alerts
|

An Individual, Community-Based Treatment for Obese Children and Their Families: The Solution-Focused Approach

Abstract: Background: This study evaluates an individual, community-based treatment for obese children and their families. In this program, a treatment team applied solution-focused techniques to develop a custom-made treatment plan in collaboration with the participants. The treatment plan consisted of community-based lifestyle activities. Methods: 559 obese children with an average BMI z-score of 2.76 ± 0.54 took part in the 12-month study, and 372 children with an average BMI z-score of 2.75 ± 0.52 took part in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…About 6% of all 2- to 19-year-olds in the United States have severe obesity (25). Although the CDC (1) cautioned about extrapolating beyond the range of the data used to estimate the LMS measures (3 rd through 97 th percentiles, corresponding to z-scores of ±1.88), BMIz continues to be widely used for children who have extreme BMI values (8,2631). Our results emphasize that BMIz is a poor BMI metric among these children, as the conversion of very high BMIs to z-scores is strongly influenced by the L and S measures in the CDC growth charts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 6% of all 2- to 19-year-olds in the United States have severe obesity (25). Although the CDC (1) cautioned about extrapolating beyond the range of the data used to estimate the LMS measures (3 rd through 97 th percentiles, corresponding to z-scores of ±1.88), BMIz continues to be widely used for children who have extreme BMI values (8,2631). Our results emphasize that BMIz is a poor BMI metric among these children, as the conversion of very high BMIs to z-scores is strongly influenced by the L and S measures in the CDC growth charts.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation and confounding of very high BMIz values could be particularly problematic in longitudinal studies that focus on children with obesity (8,2628,32). As these children age during follow-up, the extent of the compression of very high BMIz values will vary based on the values of L and S in the growth charts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the report for the CDC growth charts (Kuczmarski et al, 2002) cautioned about extrapolating outside the 3rd and 97th percentiles of BMI, BMI z remains widely used in studies that include large numbers of children with very high BMIs (Hampl et al, 2016; Kreier et al, 2013; McCormick et al, 2014; Smego et al, 2017; Wang et al, 2015). We have shown that, among children with severe obesity, BMI z levels are only weakly associated with other measures of body size (Freedman et al, 2017a) and the current results highlight the drawbacks of attempting to assess longitudinal BMI z changes.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolated z -scores based on the CDC growth charts are widely used among children who have very high BMIs (Baughcum et al, 2015; Hampl et al, 2016; Kreier et al, 2013; Smego et al, 2017; Wang et al, 2015). However, BMI z values for extremely high BMIs can differ substantially from the empirical estimates (Flegal et al, 2009), have an effective upper limit (Woo, 2009) and are strongly influenced by sex and age.…”
Section: Discussionmentioning
confidence: 99%